Effect of tin on microstructure and mechanical properties of compacted graphite iron. (3rd September 2015) - Lyu, Y.; Sun, Y.; Liu, S.; Zhao, J.
Abstract : This experiment investigated the effect of tin in an amount up to 0·121 wt-% on the microstructure and mechanical properties of compacted graphite iron. Graphite and matrix evolution was emphasised with the help of scanning electron microscopy. The results indicate that Sn in experimental range reduces graphite size. Pearlite quantity would increase with the increasing Sn and reaches over 95% when Sn is >0·057 wt-%. Sn helps to narrow the lamellar spacing of pearlite from sorbitic pearlite (320 nm) to troostitic pearlite (83 nm) when Sn increases from 0·003 to 0·057 wt-%. Appropriate Sn addition promotes the tensile strength and impact toughness, and the samples containing 0·057 wt-%Sn perform the highest values of 410·7 MPa and 9·11 J cm − 2 respectively. Elongation declines with increasing Sn content because of the emergence of more pearlite. Samples containing excessive Sn experience sharp deterioration in mechanical properties due to brittle cementite.